E-GOVERNMENT AND PUBLIC SERVICE DELIVERY: AN ANALYSIS OF THE “LAPOR!” CITIZEN COMPLAINT SYSTEM’S EFFECTIVENESS AND CHALLENGES - Agustinus Lambertus Suban; ahmed Al-Fahad; Hale Y?lmaz; Ahmet Demir (Yayasan Adra Karima Hubbi, 2025)
E-government platforms like Indonesia’s “Lapor!” citizen complaint system (CCS) aim to enhance public accountability. However, a persistent gap exists between this technological promise and the bureaucratic challenges of ensuring tangible resolution, leading to digital disillusionment. This study evaluates the effectiveness of “Lapor!” and identifies institutional challenges. It analyzes quantitative performance indicators and triangulates them with the qualitative experiences of citizens and government administrators. A sequential explanatory mixed-methods design was used, involving quantitative analysis of 50,000 system records (2023-2024) and 80 semi-structured interviews with citizens and administrators. Findings reveal a low resolution rate (38.7%) and significant delays (Mean response: 14.2 days), statistically linked to inter-agency “ping-ponging.” Qualitative data identified citizen “Digital Disillusionment” and administrator “Institutional Ambiguity” as key explanatory themes. “Lapor!” succeeds as a digital intake system but fails as an accountability mechanism. The ineffectiveness stems not from technology but from unresolved institutional challenges, primarily the lack of an empowered arbiter for inter-agency disputes.